Bersama Menentukan Kehamilan Dalam Pernikahan - Khusnul Khotimah, Umi (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2021)
The concept of partnership and equality in marriage as mentioned in the Qur'an with the term "zawj" (couple). That is the key to harmony in the family so as to achieve sakinah, mawaddah and rahmah. Marriage is not only to channel sexual desires in a halal manner, but also in order to create peace in society starting from a small family, namely husband and wife. In addition, marriage is also intended for the process of reproduction for the continuation of life on earth. Because it is the wife who carries out the heavy reproductive process, she must be involved in determining how many children are expected and when she is ready to undergo pregnancy. The husband does have a contribution, but it is only light, namely fertilizing.